Aplicação de técnicas de sensoriamento remoto no monitoramento de sedimentos do reservatório da UHE Sinop - Simões, Juliana Marestoni (2020)
Installations used for the production of hydroelectric energy are today the main supply of energy demand in Brazil and besides being a source of renewable generation, they stand out for their economic competitiveness. Although the price of its production is low, the formation of the reservoir of a hydroelectric plant causes changes in the morphological profile of the river, which, over time, induced by anthropic interference, directly influence the upstream sedimentation and downstream erosion. Hence the need to characterize and evaluate the situation of sediment production in projects with reservoir formation. In this sense, this work applied different techniques for monitoring the hydrosedimentological behavior of UHE Sinop. The data were obtained by collecting sediments in the field (observed) and applying the NDWI index (estimated) on satellite images. Statistical analyzes were performed in order to verify the existence of a significant difference between the observed and estimated data and, later, the efficiency of the data estimated by the NDWI index was verified. The results obtained indicated that the Index of the Normalized Difference of water is not sufficiently capable of replacing the traditional collections in the field, but they can be used as a support tool for continuous and alert monitoring, as it makes it possible to investigate the origin and displacement of sediments. in suspension.